Studies in cholestrol metabolism - Lewis, Barry (Department of Public Health and Family Medicine, 2020)
The biochemistry of the steroids is of unique interest; no other group of relatively simple substances plays so versatile a role in biology. On the one hand are many highly potent steroids occurring in minute quantities e.g. sex hormones, corticosteroids, the vitamins D and the cardiac glycosides. In sharp contrast are certain sterols, exemplified in the animal kingdom by cholesterol - familiar, abundant, easily determined, yet singularly obscure in their physiological significance. In some restricted fields the functions of cholesterol are known. It is a precursor of the adrenocortical hormones (perhaps not an obligatory one ), and is probably important in the biosynthesis of sex hormones too. Present in the skin is 7-dehydrocholesterol, converted to vitamins D by ultraviolet light. Cholesteryl esters are found in large quantities, together with sphingomyelin, in the myelin sheaths of nerve fibres, where these lipids may have an insulating function necessary at least for saltatory conduction.